Pengaruh Gaya Kepemimpinan Demokratis, Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Dinas Perkebunan dan Hortikultura Provinsi Sulawesi Tenggara - Gunawan Laliasa; Muh. Nur; Rince Tambunan (SIGMA: Journal of Economic and Business, 2018)
The purpose of this study is to analyze and explain the role of the democratic leadership style, work environment and work motivation on employee performance either partially or simultaneously to the employees of the office of Crops and Horticulture in Southeast Sulawesi. The unit of analysis is the study of office workers Crops and Horticulture Department of Southeast Sulawesi Province. Respondents were sampled as many as 61 employees. Data was collected by questionnaires followed by in-depth interviews. The analytical method used in testing hypotheses is multiple linear regression. Qualitative information is used to dig additional information related to the results of hypothesis testing. The results of this study indicate that: there is significant influence simultaneously between democratic leadership style and motivation impact on improving the performance of employees. No significant difference between the working environment to increase employee performance. Improved democratic style of leadership can significantly affect employee performance improvement as well as increased motivation to work can significantly affect employee performance improvement.